Stable Lewis Base Adducts of Tetrahalodiboranes: Synthetic Methods and Structural Diversity. Issue 36 (24th May 2019) - Englert, Lukas; Stoy, Andreas; Arrowsmith, Merle; Muessig, Jonas H.; Thaler, Melanie; Deißenberger, Andrea; Häfner, Alena; Böhnke, Julian; Hupp, Florian; Seufert, Jens; Mies, Jan; Damme, Alexander; et al.
Abstract: A series of 22 new bis(phosphine), bis(carbene), and bis(isonitrile) tetrahalodiborane adducts has been synthesized, either by direct adduct formation with highly sensitive B2 X4 precursors (X=Cl, Br, I) or by ligand exchange at stable B2 X4 (SMe2 )2 precursors (X=Cl, Br) with labile dimethylsulfide ligands. The isolated compounds have been fully characterized using NMR spectroscopy, elemental analysis, and, for 20 of these compounds, single‐crystal X‐ray diffraction, revealing an unexpected variation in the bonding motifs. In addition to the classical B2 X4 L2 diborane(4) bis‐adducts, certain more sterically demanding carbene ligands induce a halide displacement which led to the first halide‐bridged monocationic diboron species, [B2 X3 L2 ]A (A=BCl4, Br, I). Furthermore, low‐temperature 1:1 reactions of B2 Cl4 with sterically demanding N‐heterocyclic carbenes led to the formation of kinetically unstable mono‐adducts, one of which was structurally characterized. A comparison of the NMR spectra and structural data of new and literature‐known bis‐adducts shows several trends pertaining to the nature of the halides and the stereoelectronic properties of the Lewis bases employed. Abstract : Introducing the diborane family : 22 tetrahalodiborane bis(base) adducts and two unstable mono(base) adducts were synthesized by the addition of carbenes, phosphines, and isonitriles to highly sensitive B2 X4 or by ligand exchange at stable B2 X4 (SMe2 )2 precursors. NMR spectroscopy and crystallographic studies revealed a variety of structural motifs, from sp 2 –sp 3 ‐diboranes and sp 3 –sp 3 ‐diboranes in staggered anti and gauche conformations to novel halide‐bridged diboron cations.